2016
DOI: 10.1515/aut-2015-0028
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Properties of Syntactic foam Reinforced by Warp Knitted Spacer Fabric

Abstract: The aim of this study was to investigate the flexural behaviours of syntactic foam reinforced by warp knitted spacer fabric (SF-WKSF). Seven kinds of SF-WKSF samples were fabricated by warp knitted spacer fabric (WKSF) with structural parameters including surface layer structures, inclination-angle and fineness of spacer yarns, different microballoons types and contents. The flexural tests were carried out and the bending properties of SF-WKSF were analysed based on the strength and modulus values obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…maintained 2 to 5 vol % nanoclay in epoxy syntactic foams, an increase in flexural strength was observed with the incorporation of nanoparticles in syntactic foams and flexural strength was observed to depend on the nanoclay volume fraction. In addition, Zhi and Long investigated the flexural behaviors of syntactic foam reinforced by warp knitted spacer fabric (SF‐WKSF), results indicated that the SF‐WKSF showed higher flexural strength compared to neat syntactic foam with almost no impact on the density of composites. Zhang and Ma treated hollow carbon microspheres with a coupling agent of glutaric dialdehyde to improve the fracture toughness of phenolic syntactic foams, it was found that better interfacial adhesion could be induced from coupling agent treated hollow carbon microspheres, hence resulted in increasing the fracture toughness and the maximum fracture toughness values occurred at 28.12 vol %.…”
Section: Introductionmentioning
confidence: 99%
“…maintained 2 to 5 vol % nanoclay in epoxy syntactic foams, an increase in flexural strength was observed with the incorporation of nanoparticles in syntactic foams and flexural strength was observed to depend on the nanoclay volume fraction. In addition, Zhi and Long investigated the flexural behaviors of syntactic foam reinforced by warp knitted spacer fabric (SF‐WKSF), results indicated that the SF‐WKSF showed higher flexural strength compared to neat syntactic foam with almost no impact on the density of composites. Zhang and Ma treated hollow carbon microspheres with a coupling agent of glutaric dialdehyde to improve the fracture toughness of phenolic syntactic foams, it was found that better interfacial adhesion could be induced from coupling agent treated hollow carbon microspheres, hence resulted in increasing the fracture toughness and the maximum fracture toughness values occurred at 28.12 vol %.…”
Section: Introductionmentioning
confidence: 99%
“…7 Compressive Stress-strain curve comparison of calcium carbonate coated SFs and cementite coated SFs Table 2 shows the specific tensile strength and specific flexural strength against percentage volume concentration. Literature reports shows that the flexural strength, tensile strength and elastic modulus are enhanced by the filler [48,49]. In the case of the calcium carbonate shell coating, the specific tensile strength increases and the specific flexural strength decreases with increase in volume percentage (%) of the epoxy HMs.…”
Section: Flatwise Orientationmentioning
confidence: 99%
“…Syntactic foams are defined as closed pore foams which are formed by embedding hollow microballoons into matrix [1]. The hollow microballoons are usually made up of glass, phenolic, carbon or metal, while the matrixes are usually thermosetting resins [2].…”
Section: Introductionmentioning
confidence: 99%